NOTES FOR NOTES. - SAUCEDA, JONATHAN (Notes, 2025)
The article announces the 2025 award winners recognized by the Music Library Association (MLA) for their contributions to music librarianship and research. Notable recipients include Alexandra Martinez and Divya Ramesh, who received the Diversity Scholarship for their work in music therapy and accessibility, and Houman Bezahdi, awarded the Walter Gerboth Award for his research on McGill University's music library. Other awards highlight significant projects and contributions from various individuals, including Jennifer Ward's research on historical music codes and Scott Gleason's work related to the Library of Congress. The article also acknowledges the leadership of past presidents during the COVID-19 pandemic and the contributions of web managers to the association's online presence.